Accessing nature: Agrarian change, forest laws and their impact on an adivasi economy in colonial India - Gupta Sanjukta (Conservation & Society, 2009)
This article discusses how changing access to nature impacted an adivasi people, the Hos of Singhbhum. Without romanticizing the pre-British past, it may be argued that for the Hos of the time there had been dependence both on the forest and on cultivation, which had ensured them a minimum livelihood. This paper explores how their access to nature gradually diminished under colonial rule through the twin governmental policies of expansion of the agrarian frontier and restriction of the forests to the indigenous population. This led to the sedentarisation of the adivasis, further contributing towards agrarian expansion in India. However, this article argues that the extension of cultivation did not, however, benefit the Hos. Instead, the nature of the increase in acreage in Singhbhum, led to new agricultural practices, which, together with the restrictive forest laws and lack of new irrigation facilities, led to an agrarian crisis in the region, forcing the Hos to leave their lands and seek their fortunes elsewhere.